The tale of obesity: challenges and solutions (Faculty of Medicine Universitas Indonesia, 2003)
Obesity has struck with all its might and the results are the increased world-wide prevalence along with increased mortality rate and other obesity-related diseases. Genetic, hormonal and environmental factors interact to cause obesity. Very low calorie diet and physically active lifestyle are the primary means to treat obesity. Additional intervention is by pharmacological treatment, using two new drugs, namely cyclobutane methanamine HCl and tetra hidrolipstatin that are potential for the management of obesity. Another way to solve this problem is by performing a surgery. In conclusion, patients should consult their physicians in order to decide which methods are the most effective to find a solution to combat obesity. (Med J Indones 2003; 12: 53-62) Keywords: epidemic, genetic, leptin, cardiovascular disease, diabetes, gastric bypass, laparoscopic banding